Designing a permeable reactive barrier to treat TCE contaminated groundwater: Numerical modelling / Diseño de una barrera permeable reactiva para el tratamiento de aguas subterráneas contaminadas con tricloroetileno: modelo numérico - Grajales-Mesa, S. Johana; Malina, Grzegorz; Kret, Ewa; Szklarczyk, Tadeusz (Tecnología y ciencias del agua, 2024)
A 3-D groundwater numerical model was developed with the software Visual MODFLOW, to design a PRB with brown coal and compost as reactive materials to treat contaminated groundwater with trichloroethene (TCE) in the vicinity of Nowa DÄ™ba waterworks (South-East Poland). The results of the analysis allowed the evaluation of the flow changes due to the installation of diverse PRB systems (continuous wall, funnel and gate) and proposed the optimum configuration, length and thickness of the PRB. Furthermore, the effect of decreasing hydraulic conductivity of the reactive materials over time, and its impact on key design parameters, such as: Capture zone, residence time and discharge rate were also evaluated. Simulation results suggest that the best design for the contaminated site is a funnel and gate system with two funnels and one gate (1 310 m long and 3 m thick). In addition, results were used to select the location of downgradient monitoring wells to assess PRB performance.